Quality of Palliative Care in Children with Cancer: A Descriptive Cross-sectional Study in North of Iran - Somaye Pouy; Zahra Taheri Ezbarami; Maryam Rassouli; Bahram Darbandi; Saman Maroufizadeh; Nazila Javadi Pashaki (مجله دانشگاه علوم پزشکی گیلان)
Background: Providing high-quality palliative care, which is one of the basic rights of children with cancer, will lead to the improvement of the quality of life and satisfaction of the child and family. It is important to evaluate the quality of care in order to take corrective actions. Objective: The present study was conducted with the aim of determining the quality of palliative care for children with cancer in northern Iran Methods: This descriptive cross-sectional study was conducted on 200 parents of children with cancer who referred to the 17-Shahrivar educational and remedial center of Rasht, 2023. The samples were selected by convenience sampling methods according to inclusion criteria. Inclusion criteria were parents who had a child with cancer, were interested in participating in the study and had the ability to read. Exclusion criteria were failure to complete the questionnaires and the presence of any mental disorders or physical illness in the parents that prevented their participation in the study. The instrument used included the Palliative Care Quality Questionnaire (QCPCI). This questionnaire has 15 items and 4 dimensions (communication with family, family participation, information sharing among health workers, support of siblings), the answer to each item includes a range of scores from 0 (never) to 4 (always) and the total score ranges from zero to 100. After entering data into SPSS version 22 software, data were analyzed using descriptive statistical tests. Results: The average age of the parents was 37.83 ± 5.86. The average quality of palliative care score for children with cancer was 29.54 ± 0.34. The lowest average score was related to the dimension of supporting of siblings (4.1 ± 0.34). Conclusion: The findings showed that the quality of palliative care provided to children with cancer is lower than average and needs more attention in some aspects, especially the support of siblings. In this regard, it is recommended to provide proper planning to improve these dimensions and provide high quality palliative care in this population